Employee homogeneity and perceptions of organisational fit : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Marshall, Beverley Anne (Massey University, 1991)
Popular management literature suggests that a strong culture is important for the success of an organisation. A logical outcome of this belief is that it is important that employees should 'fit' - that is, employees' values should be congruent with those of the organisation. Schneider's (1987) Attraction-Selection-Attrition (ASA) theory argues that, over time, forces operate to ensure that an increasingly more homogeneous group of employees make up an organisation. In a test of ASA theory, the present study used the Work Aspect Preference Scale (Pryor, 1983) to assess the homogeneity of the managerial staff of a manufacturing organisation (N = 35) and a comparison group of 42 executive MBA students. As an extension of the attrition component of the model, it was hypothesised that those employees who remain in the organisation would be perceived as having better organisational fit. Kelly's (1955) repertory grid technique was used to identify those characteristics the organisation believed essential for success. These constructs were used to develop an Organisational Fit scale which was then applied to a group of 34 managers. Some marginal support was found for Schneider's ASA theory, and analysis of differences between the two groups did reveal significant differences on three work aspects. The hypothesis that employees of longer tenure would rate more highly on the Organisational Fit scale was not supported. Implications for the homogeneity hypothesis are discussed, and suggestions are made for further research on this concept, and for further study of organisational fit.
Keywords: Corporate culture; Organisational culture; Leadership; Management